2008
DOI: 10.1016/j.eneco.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the importance of oil-related revenues in total fiscal income for Mexico

Abstract: Revenues from oil exports are an important part of government budgets in Mexico. A time-series analysis is conducted using monthly data from 1990 to 2005 examining three different specifications to determine how international oil price fluctuations and government income generated from oil exports influence fiscal policy in Mexico. The behavior of government spending and taxation is consistent with the spend-tax hypothesis. The results show that there is an inverse relationship between oil-related revenues and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Lebih lanjut, menurut [23], [25], menyatakan bahwa kebijakan fiskal mengacu pada cara pemerintah mengatur sumber pendapatan dan pengeluaran pendapatan. Dengan kata lain, kebijakan fiskal menjelaskan mengenai dari mana pendapatan negara berasal, sumber pendapatan apa yang paling utama, dan jalur pengeluaran apa yang paling penting, serta bagaimana cara mendistribusikan pendapatan tersebut.…”
Section: Kajian Pustakaunclassified
“…Lebih lanjut, menurut [23], [25], menyatakan bahwa kebijakan fiskal mengacu pada cara pemerintah mengatur sumber pendapatan dan pengeluaran pendapatan. Dengan kata lain, kebijakan fiskal menjelaskan mengenai dari mana pendapatan negara berasal, sumber pendapatan apa yang paling utama, dan jalur pengeluaran apa yang paling penting, serta bagaimana cara mendistribusikan pendapatan tersebut.…”
Section: Kajian Pustakaunclassified
“…However, despite the vastness of literature on the macroeconomic consequence of oil price shocks as well on an optimal fiscal policy of oilproducing economies, only a few studies have actually evaluated the impact of oil price shocks on the fiscal activity of such economy.In this regard particularly in recent time, studies by Aregbeyen and Fasanya [17] as well as Aregbeyen and Kolawole [18] for the example of Nigeria, Anshasy and Bradley [19] for the cases of selected oil exporting countries, Farzanegan [20] for Iran, Jbir and Zouari-Ghorbel [21] Tunisia, Farzanegan and Markwardt [22] Iranian economy, Reyes-Loya, M. and Blanco [23] and Tijerina-Guajardo and Pagán [24] for Mexico. Some of these studies concluded that oil prices influence fiscal policy and that can be a key propagation mechanism for transmitting oil price shocks to the domestic economy ( [25,26,27,28]).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Reyes-Loya and Blanco [6] also in their study, evaluated the importance of the measuring the oil revenues in Mexico's total revenues. Since revenues from oil exports, make an important part of the Mexican governments budget revenues, using monthly data from 1990 to 2005, they studied three different characteristics to determine the impact of international oil price fluctuations on government revenues and government financing ultimately policies in Mexico.…”
Section: Literature Reviewmentioning
confidence: 99%